PENGARUH ORGANISASI KEMAHASISWAAN TERHADAP PEMBENTUKAN KARAKTER KEPEMIMPINAN MAHASISWA DI STAI MA’HAD ALY AL-HIKAM MALANG - Halimatus Sa’diyah; Siti Mutholingah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
In order to preserve justice and the truth, student organizations and movements support students in expressing their goals. Along with developing their interests, skills, and innovations, students can also become more perceptive and logical. The purpose of this study is to ascertain whether student groups at the Islamic College "Ma'had Aly Al-Hikam" in Malang have an impact on the development of leadership qualities. Quantitative research methodologies are used in this work. Researchers utilize questionnaires to gather data. Validity testing, reliability tests, traditional assumption tests, and hypothesis tests utilizing basic linear regression tests are all used by researchers during the data analysis and processing process. It is possible to draw the conclusion that student organizations significantly impact the development of leadership character based on the data analysis results. This can be demonstrated by comparing the significance value with a probability value of 0.05, which is the outcome of the simple linear regression analysis test. A significance value of 0.001 <0.05 was determined using the Coefficients table's significance value. According to this study, student organizations have a 76.4% impact on how leadership character is formed; other factors account for the remaining 23.6%. Furthermore, it is believed that the independent variable has a significant impact on the dependent variable, as indicated by the R-Square determination coefficient (R2) of 0.764. This suggests that H1 is accepted and the hypothesis Ho is rejected. Thus, it can be said that the variable of leadership character building (Y) is influenced by the student organization variable (X).